1995
DOI: 10.1111/j.1540-8159.1995.tb02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Termination and Acceleration of Ventricular Tachycardia with Autodecremental Pacing, Burst Pacing, and Cardioversion in Patients with an Implantable Cardioverter Defibrillator

Abstract: This multicenter study reports the outcome of ventricular tachycardia (VT) therapy (conversion or acceleration) and the relationship to initial tachycardia cycle length and other clinical variables using an implantable device with the capability of autodecremental or burst pacing, cardioversion, and defibrillation. The device was implanted in 444 patients (mean age 58 +/- 15 years) with 1,240 episodes of VT induced with noninvasive programming and reported in a multicenter database. Only the first sequence att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…Cycle length of ATP stimulus, number of ATP pulse, and site of ATP stimulation were all contribution factors of the efficacy of ATP therapies 16. In a study with induced VT, with more pulses in ramp stimulation, the incidence of ATP acceleration was higher, but there were no similar findings in burst stimulation 15. In spontaneous VT study, Nasir et al 20 found no difference between different burst numbers in ATP acceleration either.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycle length of ATP stimulus, number of ATP pulse, and site of ATP stimulation were all contribution factors of the efficacy of ATP therapies 16. In a study with induced VT, with more pulses in ramp stimulation, the incidence of ATP acceleration was higher, but there were no similar findings in burst stimulation 15. In spontaneous VT study, Nasir et al 20 found no difference between different burst numbers in ATP acceleration either.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter VTCLs are associated with less possibility for ATP to penetrate the excitable gap of the reentrant circuit. Hammill et al 15 and Calkins et al 8 reported that the incidence of ATP acceleration in VTs with VTCL<300 ms was higher than with VTCL ≥300 ms in induced VTs. However, Peters et al 6 failed to find the same result in spontaneous VTs with VTCL<300 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21-24 A multicenter, retrospective study by Hammill and colleagues 25 evaluated induced episodes with 357 episodes treated with burst pacing and 700 episodes treated with ramp. The burst pacing was more likely than ramp pacing to accelerate VT events with shorter cycle lengths, and low ejection fraction and VT cycle length less than or equal to 300 ms were factors that were associated with ATP accelerating the VT. 25 The Project for the Investigation and Treatment of Ventricular Arrhythmias: a General Observational Registry on Antitachycardia Pacing Efficacy (PITAGORA ICD) Trial was a blinded, multicenter, randomized controlled trial that randomized 103 patients to 88% coupling interval burst and 103 patients to 91% coupling interval ramp ATP. 26 The median follow-up in the trial was 36 months, and burst pacing terminated 75% of fast VT episodes (cycle length between 240 ms and 320 ms), whereas ramp terminated 54% of fast VT episodes (P 5 .015).…”
Section: Mechanics Of Antitachycardia Pacingmentioning
confidence: 99%
“…Die durchschnittliche VTCL unter antiarrhythmischer Medikation war zwar signifikant, aber nur gering länger als ohne Medikation (356 ± 59 vs. 347 ± 44 ms, p < 0,001). Zu ähnlichen Ergebnissen kamen Waldecker et al (15) und Hammill et al (1). In ihren Analysen konnte ebenfalls, bei einer Anhebung der Zykluslänge, die Erfolgsquote nicht verbessert werden.…”
Section: Antiarrhythmische Medikationunclassified